Ethical standards for psychological practice in the UAE: current status and aspirations. Issue 3 (3rd April 2023) - Al-Darmaki, Fatima; Yaaqeib, Saad Ibrahim; Partridge, Susan
ABSTRACT: There is a growing body of global research demonstrating the significance of mental health to individuals' overall happiness and productivity. The research evidence has encouraged governmental agencies in the United Arab Emirates (UAE) to divert more attention toward the provision and development of mental health services. As the sector grows, one of the first issues of concern is the adherence to a unified set of ethics of practice. The purpose of this paper is to present and discuss the existing ethical codes of conduct relevant to the mental health profession in the unique context of the UAE. Specifically, this discussion will focus on the interaction of cultural factors with the ethical standards of confidentiality, informed consent, and multiple relationships. This paper provides an initial reference for researchers and practitioners to explore regional issues of ethical standards in mental health services.